Acute nutritional ketosis: implications for exercise performance and metabolism - Cox, P. J.; Clarke, K. (Extreme Physiology & Medicine, 2014)
Ketone bodies acetoacetate (AcAc) and D-ß-hydroxybutyrate (ßHB) may provide an alternative carbon source to fuel exercise when delivered acutely in nutritional form. The metabolic actions of ketone bodies are based on sound evolutionary principles to prolong survival during caloric deprivation. By harnessing the potential of these metabolic actions during exercise, athletic performance could be influenced, providing a useful model for the application of ketosis in therapeutic conditions. This article examines the energetic implications of ketone body utilisation with particular reference to exercise metabolism and substrate energetics.